2018
DOI: 10.1180/clm.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of organo-kenyaites: thermal stability and their effects on eosin removal characteristics

Abstract: Organo-kenyaites were prepared from a cetyltrimethylammonium hydroxide (C16TMAOH) solution and solid sodium kenyaite (Na2Si22O45.10H2O) mixture. The effect of the initial cetyltrimethylammonium solution on the structure of the intercalated materials was investigated by CHN analyses, X-ray diffraction (XRD), thermogravimetric analysis, SEM, and 29Si and 13C solid NMR techniques. For C16TMAOH concentration 0.25 mM, the Na+ cations were fully exchanged. Initial C16TMAOH concentrations higher than 0.25 mM had litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
42
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(60 citation statements)
references
References 59 publications
18
42
0
Order By: Relevance
“…In good agreement with the XRD data, the content of the organic cations did not affect the features of the spectra, indicating that the cations mainly adopted the trans conformation ( Figure 3). Similar data were reported for organo-kenyaites and organo-clays with closely packed organic contents [23,25,33]. …”
Section: Solid-state Nmr Studiessupporting
confidence: 75%
See 4 more Smart Citations
“…In good agreement with the XRD data, the content of the organic cations did not affect the features of the spectra, indicating that the cations mainly adopted the trans conformation ( Figure 3). Similar data were reported for organo-kenyaites and organo-clays with closely packed organic contents [23,25,33]. …”
Section: Solid-state Nmr Studiessupporting
confidence: 75%
“…The EDX data indicated that traces of Na cations occurred with high loadings of organic surfactants. In the case of the similarly layered structure kenyaite, only a partial exchange occurred [33]. This result was not the same for clay minerals, where the uptake amount of C16TMA largely exceeded the CEC values [21].…”
Section: C H N Elemental Analysismentioning
confidence: 64%
See 3 more Smart Citations